2018
DOI: 10.5650/jos.ess17212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Roasting Temperatures on the Properties of Bitter Apricot (<i>Armeniaca sibirica</i> L.) Kernel Oil

Abstract: Volatile compounds and quality changes of bitter apricot (Armeniaca sibirica L.) kernel oil (AKO) with different roasting conditions were determined. Bitter apricot kernels were roasted at 120, 130, 140 and 150°C for 15 min. Unroasted bitter apricot kernel oil was used as the control. Quality indicators included color, acid value and peroxide value, fatty acids, total phenols and oxidative stability. Peroxide values of the tested oils were 0.46-0.82 meq/kg, acid values were 0.60-1.40 mg KOH/g, and total phenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
4
4
0
Order By: Relevance
“…The L *, a *, and b * values of oil from unroasted pine nut kernels were 95.92, −5.12, 46.42, and 95.79, −5.49, 57.78 for the PK and PKS samples, respectively. The a * and b * values increased significantly ( p < .05), while the L * value decreased significantly ( p < .05) for both varieties by increasing the roasting time and temperature, and the trends in color values were in accordance with a study for oils from roasted bitter apricot kernels (Jin et al., 2018). The L * values did indeed decrease as roasting temperatures rose in the PK and PKS samples, and reached the minimum values at 180℃ for 30 min, which were 59.12 and 57.1, respectively.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The L *, a *, and b * values of oil from unroasted pine nut kernels were 95.92, −5.12, 46.42, and 95.79, −5.49, 57.78 for the PK and PKS samples, respectively. The a * and b * values increased significantly ( p < .05), while the L * value decreased significantly ( p < .05) for both varieties by increasing the roasting time and temperature, and the trends in color values were in accordance with a study for oils from roasted bitter apricot kernels (Jin et al., 2018). The L * values did indeed decrease as roasting temperatures rose in the PK and PKS samples, and reached the minimum values at 180℃ for 30 min, which were 59.12 and 57.1, respectively.…”
Section: Resultssupporting
confidence: 85%
“…A similar trend was also found in p‐AV (Figure 1c,f), suggested the increase in the content of primary and secondary oxidation compounds. In summary, the oxidative stability of pine nut oil could be enhanced by appropriate roasting treatment, and similar results could be found in the researches for pistachio oil (Rabadán et al., 2018) and apricot kernel oil (Jin et al., 2018). The improved oxidative stability of oil from roasted pine nuts could be attributed to the synergistic antioxidant effect of browning substances that were produced in the roasting process and increased bioactive compounds.…”
Section: Resultssupporting
confidence: 77%
“…The study has shown that the composition and content of volatile compounds in peanut oil changed significantly after roasting pretreatment, and the contents of O‐heterocyclic compounds and N‐heterocyclic compounds accounted for a relatively high proportion, of which 20 pyrazines were considered as key contributors to the typical nut and roasting aroma of peanut oil (Liu et al., 2011). Similar studies have been done in sesame oil, rapeseed oil, palm kernel oil, almond oil, pumpkin seed oil, and peony seed oil (Jin et al., 2018; Jin et al., 2019; Jing et al., 2020; Potočnik & Košir, 2017; Yan et al, 2012; Zhang et al., 2016). Microwave, as a new heating technology, is gradually applied to oil processing.…”
Section: Introductionsupporting
confidence: 58%
“…Free amino acids and monosaccharides are considered important flavor precursors for the formation of volatile compounds with unique flavors, such as pyrazine, during roasting (Marzocchi et al., 2017). A previous study showed that pyrazines are typical volatile compounds detected in roasted seeds, including bitter apricot kernel, hazelnut, sesame seeds, peanut, and so on (Jin et al., 2018; Marzocchi et al., 2017; Park et al., 2011). In the present study, five pyrazines were identified: 2‐methylpyrazine, 2,5‐dimethylpyrazine, 2,3‐dimethyl‐5‐ethylpyrazine, 2‐ethyl‐6‐methylpyrazine, and 2,6‐dimethylpyrazine.…”
Section: Resultsmentioning
confidence: 99%